Synchronous papillary thyroid carcinoma and breast ductal carcinoma: A rare case report and literature review. Issue 7 (February 2017) - Zhong, Jinjing; Lei, Jianyong; Jiang, Ke; Li, Zhihui; Gong, Rixiang; Zhu, Jingqiang
Abstract: Background: The incidences of both thyroid cancer and breast cancer have been rising in recent years; however, it is very rare to find a single person with both of these cancers. Only a few cases of synchronous thyroid and breast cancer have been published, and even fewer cases have been reported in older patients (>60 years). Case summary: The current study presents a case of synchronous papillary thyroid carcinoma and breast ductal carcinoma in an elderly patient. The patient first underwent a mastectomy and axillary lymphadenectomy in our department, followed by a total thyroidectomy and lymphadenectomy of the left lateral region of the neck 1 month later. Postoperative pathological examination identified invasive ductal carcinoma of the breast and papillary carcinoma of the thyroid. Over almost half a year of follow-up, the patient has exhibited no evidence of recurrence or metastasis, as demonstrated by careful ultrasound examinations. Herein, we not only report this case but also present a systematic review of the causes, diagnosis, and treatment of synchronous breast and thyroid cancer. Conclusion: Although synchronous primary tumors of the thyroid and breast are very rare, they remain a possibility; therefore, more attention should be paid to these cases.